High-sulfur capacity and regenerable Zn-based sorbents derived from layered double hydroxide for hot coal gas desulfurization - Wu, Mengmeng (2020)
The Zn-Al mixed metal oxide (ZnAl-MMO) with a plate-like structure was derived from Zn-Al layered double hydroxide. The ZnAl-MMO with a Zn/Al molar ratio of 3:1 exhibits superior absorption ability for H2S in a simulated coal gas at 600 ℃ due to the special structure of the ZnAl-MMO. Besides ZnS, elemental sulfur is also produced during the desulfurization process. The deactivation model could well simulate the absorption behavior of H2S. The sulfidation reaction over the sorbent shows large initial reaction rate constants (1110-5390 m3 min-1  kg-1) and low activation energy (29.5 kJ mol-1). The regeneration rate of the used sorbent can reach 99.8% under the optimum conditions. The regenerated sorbents still show high sulfur capacity (ca. 30%), implying its great application potential for industrial-scale desulfurization of the hot coal gas.